2018
DOI: 10.1080/15548627.2018.1505153
|View full text |Cite
|
Sign up to set email alerts
|

The pro-oxidant adaptor p66SHC promotes B cell mitophagy by disrupting mitochondrial integrity and recruiting LC3-II

Abstract: Macroautophagy/autophagy has emerged as a central process in lymphocyte homeostasis, activation and differentiation. Based on our finding that the p66 isoform of SHC1 (p66SHC) pro-apoptotic ROS-elevating SHC family adaptor inhibits MTOR signaling in these cells, here we investigated the role of p66SHC in B-cell autophagy. We show that p66SHC disrupts mitochondrial function through its CYCS (cytochrome c, somatic) binding domain, thereby impairing ATP production, which results in AMPK activation and enhanced au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 90 publications
2
29
0
Order By: Relevance
“…In this study, we also found that OGD-induced oxidative stress was significantly inhibited by KFL, suggesting a substantial role of KFL in the redox regulation under OGD condition. P66 isoform of SHC1 (p66shc) proapoptotic ROS-elevating SHC family adaptor is an important regulator of redox homeostasis [31]. Genetic ablation of the p66Shc has been shown to reverse cognitive deficits and improve mitochondrial function in an APP transgenic mouse model of Alzheimer's disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that OGD-induced oxidative stress was significantly inhibited by KFL, suggesting a substantial role of KFL in the redox regulation under OGD condition. P66 isoform of SHC1 (p66shc) proapoptotic ROS-elevating SHC family adaptor is an important regulator of redox homeostasis [31]. Genetic ablation of the p66Shc has been shown to reverse cognitive deficits and improve mitochondrial function in an APP transgenic mouse model of Alzheimer's disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…43 However, p66shc disrupts mitochondrial function via its CYCS (cytochrome c, somatic) binding domain, impairing ATP production, activating AMP-activated protein kinase (AMPK) and enhancing autophagic flux. 44 ROS are generated by the Nox family of enzyme complexes, which catalyze the transfer of electrons from NADPH to molecular oxygen, generating O 2 . 45,46 Thus, p66Shc deficiency reduced the activation of the PHOX complex, decreasing superoxide production.…”
Section: Discussionmentioning
confidence: 99%
“…As we will discuss in the following sections, we have identified a new survival-related function of p66Shc as regulator of B lymphocyte autophagy (Onnis et al, 2018), a process that regulates B cell fate, survival and differentiation, highlighting p66SHC as a pleiotropic master regulator of lymphocyte survival.…”
Section: Pathogenic Outcomes Of P66shc Deficiency In Lymphocytesmentioning
confidence: 99%
“…Not surprisingly, p66SHC deficiency is associated with pathogenic outcomes, including autoimmunity and leukemia (Finetti et al, 2008;Capitani et al, 2010;Patrussi et al, 2019). We have recently reported a new role for p66SHC as regulator of B-cell autophagy/mitophagy and differentiation (Onnis et al, 2018). Here we will summarize our current understanding of the multifaceted role of p66SHC in lymphocyte survival and discuss the pro-autophagic/mitophagic function of p66SHC in the context of the autophagic control of B-cell development and differentiation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation